Parle, Éric, et je t'écouterai — Essai d'analyse d'un récit orokaïva - Maranda, Pierre (Anthropologica, 2022)
This text presents an analysis of the first part of an Orokai'va myth collected in the field by Eric Schwimmer, "Saruruse, Toothless Mouthless" that appeared in Parle, etje t'ecouterai : Recits et traditions des Orokalva de Papouasie-N ouvelleGuinee (Speak, and I will listen to you: Myths and traditions of the Orokai'va of Papua New Guinea) (lteanu and Schwimmer 1996). The use of the canonical formula of Claude Levi-Strauss for the analysis of myths, as practised and promoted by Schwimmer, suggests an interpretation of this account in terms of a "double twist," that is to say, a semiotic inversion through which sociological kinship overrides biological kinship at the same time as neo-local residence overrides native abode.